ANALISIS MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA DISLEKSIA KELAS III - Khotimah, Siti; Artharina, Filia Prima; Purnamasari, Veryliana; Setyawati, Ariani Nur (FKIP, PGSD, Universitas Slamet Riyadi, 2024)
The background of this research is that there are students in class III with low reading ability and often make mistakes in recognizing letters. In accordance with the existing theory, students with this condition are called dyslexic disorders. The purpose of this study is to find out that the use of audio-visual media can improve the reading ability of students with dyslexia. The type of research used by researchers is qualitative with a descriptive design. Data collection techniques used by researchers are observation, interviews, and documentation. The subjects of this study were class III students at SDN Tlogosari Kulon 01 Semarang. Researchers interviewed dyslexic students and class teachers. Based on the results of research at SDN Tlogosari Kulon 01 Semarang it was found that students with dyslexia could improve their reading ability by using audio-visual media.